Implikasi Pidana dan Perlindungan Hukum Terhadap Korban Penganiayan Anak Di Bawah Umur - Nur Fajri Fauziah Pantu (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Abuse of minors is a very serious act and requires strong legal protection. The purpose of this writing is to find out the criminal implications and legal protection for victims of abuse of minors. The type of research used in this writing is library research. Library research means research that uses written documents as data, and the data sources used in this research include primary legal materials, secondary legal materials and tertiary materials. The criminal implication of imposing criminal sanctions imposed on perpetrators of abuse of minors aims to provide justice for victims and prevent the recurrence of similar crimes. These sanctions include imprisonment, fines, or other punishments according to the level of crime committed by the offender.